Low-grade mucoepidermoid carcinoma of the parotid gland in a 5-year-old child: The youngest reported case from India (Indian Journal of Case Reports, 2026)
Mucoepidermoid carcinoma (MEC) of the parotid gland is scarce in the pediatric group and is exceedingly uncommon in children under 6 years. In spite of being the most frequent malignant salivary gland tumor in children, the majority of cases are reported in older age groups. Only a few cases in children under 5 years have been documented worldwide, and the youngest of these previously reported Indian cases was a 6-year-old child. We report a rare case of lowgrade MEC of the parotid gland in a 5-year-old boy, describing the youngest reported case from India to date. The presenting complaint was a painless parotid swelling, and pre-operative imaging and fine-needle aspiration cytology (FNAC) were suggestive of pleomorphic adenoma. FNAC has limited sensitivity in pediatric salivary gland tumors, particularly in low-grade MEC, due to superimposing cytomorphological features with benign lesions. The management comprised superficial parotidectomy with facial nerve preservation, with histopathological examination confirming low-grade MEC with clear margins. This case highlights the rarity of this condition, diagnostic pitfalls and limitations of FNAC, and the significance of histopathological confirmation.